Competition Works : Driving Microfinance Institutions to Reach Lower-Income People and the Unbanked in Peru - Rebolledo Dellepiane, Miguel Angel (International Finance Corporation, Washington, DC, 2019)
Competition from commercial banks is prompting microfinance institutions in urban areas ofPeru and other Latin American nations to provide more service to lower-income groups. Wherehigher-income clients are already served by commercial banks, microfinance institutions competeby attending to a new demographic, while continuing to serve higher-income clients wherecommercial banking services are scarce.